2011
DOI: 10.1117/1.3613926
|View full text |Cite
|
Sign up to set email alerts
|

Genetically encoded ratiometric biosensors to measure intracellular exchangeable zinc in Escherichia coli

Abstract: Zinc is an essential element for numerous cellular processes, therefore zinc homeostasis is regulated in living organisms. Fluorescent sensors have been developed as important tools to monitor the concentrations of readily exchangeable zinc in live cells. One type of biosensor uses carbonic anhydrase (CA) as the recognition element based on its tunable affinity, superior metal selectivity, and fluorescence signal from aryl sulfonamide ligands coupled to zinc binding. Here, we fuse carbonic anhydrase with a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 48 publications
2
76
0
Order By: Relevance
“…Middle and lower panels S. typhimurium SA211 (sodA-3XFLAG), SA341 (sodA-3XFLAG mntH sitABCD), MC153 (sodA-3XFLAG fepA/entF feoB), MC120 (sodB-3XFLAG), MC122 (sodB-3XFLAG mntH sitABCD) and MC154 (sodB-3XFLAG fepA/entF feoB) were grown in LB supplemented or not with cadmium 0.5 mM and epitope tagged MnSOD (middle panels) and FeSOD (lower panels) were revealed as described in ''Materials and methods'' section are below the threshold of immunodetection. In contrast, when bacteria are exposed to cadmium, it is possible to observe the simultaneous accumulation of ZnuA and ZntA, a paradoxical condition that is never observed in the absence of this toxic metal, because the two systems are normally activated at different zinc concentrations to guarantee the maintaining of adequate intracellular zinc levels (Wang et al 2011(Wang et al , 2012. The exposure to both cadmium and zinc causes a significant down-regulation of the high affinity zinc importer and a strong induction of the detoxification pump, indicating the primary role for ZntA in extrusion of both metals.…”
Section: Discussionmentioning
confidence: 96%
“…Middle and lower panels S. typhimurium SA211 (sodA-3XFLAG), SA341 (sodA-3XFLAG mntH sitABCD), MC153 (sodA-3XFLAG fepA/entF feoB), MC120 (sodB-3XFLAG), MC122 (sodB-3XFLAG mntH sitABCD) and MC154 (sodB-3XFLAG fepA/entF feoB) were grown in LB supplemented or not with cadmium 0.5 mM and epitope tagged MnSOD (middle panels) and FeSOD (lower panels) were revealed as described in ''Materials and methods'' section are below the threshold of immunodetection. In contrast, when bacteria are exposed to cadmium, it is possible to observe the simultaneous accumulation of ZnuA and ZntA, a paradoxical condition that is never observed in the absence of this toxic metal, because the two systems are normally activated at different zinc concentrations to guarantee the maintaining of adequate intracellular zinc levels (Wang et al 2011(Wang et al , 2012. The exposure to both cadmium and zinc causes a significant down-regulation of the high affinity zinc importer and a strong induction of the detoxification pump, indicating the primary role for ZntA in extrusion of both metals.…”
Section: Discussionmentioning
confidence: 96%
“…Because the CA-FP fusion is synthesized by the cell, signal peptides can be used to target the sensor to intracellular organelles, and this sensor was successfully targeted to mitochondria of mammalian cells. 53a …”
Section: General Features Of Fluorescent Sensors For Metal Ionsmentioning
confidence: 99%
“…Thus, different transporters acquire the metal from the growth medium to reach a total concentration in the submillimolar range, while transcriptionally controlled zinc uptake and efflux systems maintain the readily exchangeable "free" zinc at very low concentrations [3]. Whereas initial in vitro studies suggested that cellular "free" zinc levels are in the femtomolar range [3], more recent studies involving ratiometric zinc biosensors have shown that the in vivo "free" zinc is around 20 pM [4].…”
Section: Introductionmentioning
confidence: 99%
“…The ZnuA family belongs to the so-called cluster 9 of periplasmic solute-binding proteins (PBPs) and displays their well conserved architecture comprising a pair of (α/β) 4 sandwich domains and a connecting long, tightly packed α-helix. The distinctive characteristic of all ZnuA proteins consists of a histidine rich (His-rich) loop located at the entrance of the Zn(II) binding site at the interface between the two domains.…”
Section: Introductionmentioning
confidence: 99%